Comparative proximate composition of malaysian fermented shrimp products - Ilyanie H.Y.; Huda-Faujan N.; Ida Muryany M.Y. (Malaysian Society of Applied Biology, 2024)
Two different types of fermented shrimps locally known as belacan and cincaluk are amongst the most common fermented products consumed in Malaysia. Proximate composition of these products were analysed which include moisture, ash, protein, and fat. Total carbohydrate was calculated using difference of the value of each nutrient. Water activity, salt concentration, pH, and colour of each product were also measured for both fermented shrimp product. Results revealed that cincaluk has higher moisture, protein, ash, carbohydrate content, and water activity but lower content of sodium and pH value in comparison to belacan. The results for both products are also comparable with the other types of fermented shrimp products from different country, respectively. 2020, Malaysian Society of Applied Biology. All rights reserved.